Macrophage specificity of three anti-CD68 monoclonal antibodies (KP1, EBM11, and PGM1) widely used for immunohistochemistry and flow cytometry. Issue 7 (11th June 2004) - Kunisch, E; Fuhrmann, R; Roth, A; Winter, R; Lungershausen, W; Kinne, R W
Abstract : Objectives: To investigate the specificity of three anti-CD68 monoclonal antibodies (mAbs) for macrophages (Mφ) in immunohistochemistry (IHC) and flow cytometry (FACS). Methods: IHC was performed on cryostat sections of rheumatoid arthritis (RA) and osteoarthritis (OA) synovial membranes using the anti-CD68 mAbs KP1, EBM11, and PGM1, and the fibroblast (FB) markers CD90 and prolyl 4-hydroxylase. Expression of CD68 was also analysed by FACS on the monocytic cell lines THP-1 and U937, as well as on synovial fibroblasts (SFB), skin FB, and gingival FB (both surface and intracellular staining). Results: In IHC, there was an overlap between CD68 (mAbs KP1 and EBM11) and the FB markers CD90/prolyl 4-hydroxylase in the lining layer, diffuse infiltrates, and stroma of RA and OA synovial membranes. In FACS analysis of THP-1 and U937 cells, the percentage of cells positive for the anti-CD68 mAbs KP1 and EBM11 progressively increased from surface staining of unfixed cells, to surface staining of pre-fixed cells, to intracellular staining of the cells. Upon intracellular FACS of different FB, nearly all cells were positive for KP1 and EBM11, but only a small percentage for PGM1. In surface staining FACS, a small percentage of FB were positive for all three anti-CD68 mAbs. Conclusion: An overlap between CD68 (mAbs KP1 or EBM11) and the FB markers CD90 or prolyl 4-hydroxylase may prevent unequivocal identification of Mφ in synovial tissue by IHC or in monocytic cells and FB upon intracellular FACS. This may be due to sharing of common markers by completely different cell lineages.